2018
DOI: 10.1088/1748-9326/aab0af
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of sustained use and abandonment of clean cooking systems: lessons from rural India

Abstract: Clean cooking technologies-ranging from efficient cookstoves to clean fuels-are widely deployed to reduce household air pollution and alleviate adverse health and climate consequences. Although much progress has been made on the technical aspects, sustained and proper use of clean cooking technologies by populations with the most need has been problematic. Only by understanding how clean cooking as an intervention is embedded within complex community processes can we ensure its sustained implementation. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…A gap in this literature is studying which factors cause people to decrease or stop using their clean cookstoves. Several studies have reported that participants stop using clean cookstoves during or soon after a study period ( Hanna et al 2016 , Tigabu 2017 , Mudombi et al 2018 ), yet formal assessments of the determinants of this clean cookstove abandonment have been minimal ( Wang and Corson 2015 , Chalise et al 2018 ). We present an empirical assessment of factors that lead people to decrease and ultimately stop using their clean cookstoves—a phenomenon we term ‘clean cookstove discontinuance’—which we define as disuse of their intervention stove.…”
Section: Introductionmentioning
confidence: 99%
“…A gap in this literature is studying which factors cause people to decrease or stop using their clean cookstoves. Several studies have reported that participants stop using clean cookstoves during or soon after a study period ( Hanna et al 2016 , Tigabu 2017 , Mudombi et al 2018 ), yet formal assessments of the determinants of this clean cookstove abandonment have been minimal ( Wang and Corson 2015 , Chalise et al 2018 ). We present an empirical assessment of factors that lead people to decrease and ultimately stop using their clean cookstoves—a phenomenon we term ‘clean cookstove discontinuance’—which we define as disuse of their intervention stove.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, scientists applied systems approaches to understand user behavior in relation to interventions. For example, Kumar et al (2017) have examined behavioral dynamics at the community scale to understand the process of adopting of LPG cooking, and Chalise et al (2018) analyzed abandonment of biogas digesters and their stoves. Systems science methods applied to environmental health can be useful for:…”
Section: Systems Science Expands Implementation Science Approachesmentioning
confidence: 99%
“…• Sustaining interventions: System science approaches are essential to understand and solve implementation problems that result from feedback between technologies, social and cultural norms, and livelihood options that are nonlinear and dynamic. Chalise et al (2018) identified such feedback mechanisms in sustained use of improved biogas stoves in two communities; one community that sustained high levels of exclusive biogas use and an adjacent community that largely abandoned the technology. Using qualitative group model building and subsequent system dynamics simulation they traced the community interactions that led to solutions for technical and maintenance problems with fuel digesters and thus increased use of the cleaner technology in the one community, compared with frustration and abandonment by the other.…”
Section: Some Suggested Applications Of Systems Science To Hap and Wamentioning
confidence: 99%
See 1 more Smart Citation
“…Over the course of this time, our research portfolio and service contracts have been remained focused on the use of system dynamics in communities and human service organizations with ongoing projects and collaborations around the world including Afghanistan, Australia, Brazil, Chile, China, Ethiopia, Guatemala, Honduras, India, Kenya, Malawi, Mongolia, New Zealand, Pakistan, Panama, Singapore, United Kingdom, and the United States. Topics typically focus on various areas of service design and community engagement in social work, public health, and preventing medicine including mental health (Trani et al, 2016), “long-tails” in health disparities (Kreuter et al, 2014), access to primary care (Rose et al, 2013), housing and homelessness (Fowler et al, 2017), cancer disparities (Williams et al, 2016; Williams et al, 2018), clinical guidelines (Markham, Hovmand, and Doctor, 2017), obesity (Colditz et al, 2016; Hoehner et al, 2015; Sabounchi et al, 2014), energy security among the poor (Chalise et al, 2018; Yadama, 2013), implementation science (Proctor et al, 2011), and gender based violence (Hovmand et al, 2012).…”
Section: Dynamics Of Growthmentioning
confidence: 99%